Pengelolaan Program Induksi Guru Pemula Untuk Meningkatkan Kompetensi Pedagogik Di SMP Negeri 3 Kunduran Blora - , Sugiyarti, Prof.Dr.Bambang Sumardjoko, M.Pd, Dr.Ahmad Muhibbin, M.Sc (2017)
ABSTRACT Sugiyarti, Q100150064, email: sugiyarti1975@gmail.com, theses Management beginner teacher induction program (PIGP) in SMP Negeri 3 Kunduran Blora. Graduate school Master of Education Administration University Muhammadiyah of Surakarta. This study aims to describe the planning, implementation and evaluation of programs induction of beginning teachers (PIGP) in SMP Negeri 3 Kunduran Blora. This study is qualitative research, data collection method using interview techniques, observation and documentation. Informans include three new teachers people, three mentor teachers, headmaster and school supervisors. Collection data analysis techniques to the data, data reduction, data presentation and conclusion. Data validation techniques using triangulation data. The study states PIGP first planned in co-operation between the principal supervisor and counselor. The headmaster made a needs analysis which is then submitted to a tutor to be made a priority coaching. Novice teachers in making learning device includes lesson plans, syllabi, KKM, Kaldik, promes and prota for one year of study. In the planning stage tutor already started mentoring beginning teachers in making learning plan if novice teachers experiencing difficulties. Two the implementation of the program in the second until the ninth month. Novice teachers implement instructional accompanied and evaluated by the supervising teacher at least once every month. The induction not only pedagogis competen but profetional competen too. Three the evaluation phase conducted in the tenth and eleventh at least twice the face using a model lesson study. PIGP final value is the combined value of the appraisal conducted by the supervising teacher, the headmaster school and supervisor school .